2008
DOI: 10.1021/bi801912z
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Membrane Spanning Region of Human Heme Oxygenase-1 Mediates a Time-Dependent Complex Formation with Cytochrome P450 Reductase

Abstract: Heme oxygenase-1 (HO-1) catalyzes the oxidative degradation of heme to biliverdin, carbon monoxide, and free iron in a reaction requiring the interaction of HO-1 with NADPH-cytochrome P450 reductase (CPR). HO-1 is bound to the endoplasmic reticulum by 23 C-terminal amino acids; however, a soluble HO-1 (sHO-1) lacking this membrane spanning region has been extensively studied. The goal of this project was to characterize the effect of the C-terminal hydrophobic domain on formation of the HO-1/CPR complex. Full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…However, the recent characterization of a recombinant full-length HO-1 had indicated that the fulllength form exhibits a 2-to 3-fold greater activity relative to that of the truncated, soluble form, which was increased even further in the presence of lipid. Moreover, the C-terminal hydrophobic tail has an essential role with respect to membrane incorporation as well as in formation of a high-affinity complex with cytochrome P450 reductase, deemed essential for maximal catalytic activity [93][94][95]. The C-terminal domain is also the major point of sequence divergence between the two isozymes, especially in the presence of the HRMs in HO-2 [58].…”
Section: Looking Forwardmentioning
confidence: 99%
“…However, the recent characterization of a recombinant full-length HO-1 had indicated that the fulllength form exhibits a 2-to 3-fold greater activity relative to that of the truncated, soluble form, which was increased even further in the presence of lipid. Moreover, the C-terminal hydrophobic tail has an essential role with respect to membrane incorporation as well as in formation of a high-affinity complex with cytochrome P450 reductase, deemed essential for maximal catalytic activity [93][94][95]. The C-terminal domain is also the major point of sequence divergence between the two isozymes, especially in the presence of the HRMs in HO-2 [58].…”
Section: Looking Forwardmentioning
confidence: 99%
“…Because of the many potential interactions of CPR with other enzymes, it is important to better understand the behavior of HO-1 with CPR in a membrane environment. This requires the examination of full-length HO-1 because of the inability of the soluble form to associate with the membrane (Huber et al, 2009). The interplay between CPR and its many electron acceptors can have a significant effect on heme degradation, drug metabolism, and cholesterol synthesis, as well as fatty acid metabolism.…”
mentioning
confidence: 99%
“…Recently, our laboratory showed that the C-terminal region present on HO-1 influences both membrane incorporation and the formation of a high-affinity complex between full-length HO-1 and CPR (Huber et al, 2009). Not only does this form of HO-1 bind tightly to the membrane and CPR but also the characteristics of heme degradation by the full-length protein differ significantly from those found with the soluble enzyme, requiring re-examination of the conditions for the standard HO-1 assay.…”
mentioning
confidence: 99%
“…One reason for this is the fact that the full-length HO-1 is very unstable and susceptible to truncation that generates an inactive, soluble form (28 kDa). The C-terminal part of the protein that is cleaved causes the HO-1 to interact with membrane lipids, and its removal alters the manner by which the enzyme interacts with potential membrane binding partners (Huber, III et al, 2009;Huber, III and Backes, 2007). Most in vitro studies of HO-1 have expressed and purified a modified, but active, 30 kDa form of the enzyme that lacks the C-terminal membrane-binding sequence and is soluble as a result.…”
Section: Regulation Of Important Enzymes By Ho-1mentioning
confidence: 99%
“…This mutant is full-length and binds to lipid vesicles. The fulllength HO-1 mutant also binds much tighter to the P450 reductase and has much higher catalytic efficiency than the active, soluble form of the enzyme (Huber, III et al, 2009). Thus, studies with this mutant will finally enable researchers to understand the enzymatic capability of HO-1 with respect to those of the other potential binding partners in the endoplasmic reticulum.…”
Section: Regulation Of Important Enzymes By Ho-1mentioning
confidence: 99%